(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2022)
In the wake of post-pandemic work dynamics, there’s talent shortage worldwide, even after huge unemployment caused by temporary closing-down of businesses and disrupted economic activities due to COVID-19. There’s enormous cost involved in talent screening, assessment, and hiring after rounds of interview and selection tests, however when newly hired candidate doesn’t turn-up after receiving offer or undergoing onboarding process, whole activity-endeavor is squandered. The new age TA manager face multifold issues in identification, hunt, and sourcing of talent in the ever-dynamic working environment in post-pandemic context. The market of skilled candidates is becoming fiercely competitive in tech-enabled and AI supportive work-era, posing further question of, how and where to detect right talent in right time and at the right cost, who stays with organization at least till the time he starts generating return on investment for the organization. The biggest challenge talent acquisition managers face today is, candidates turning ghosts after selection and receiving employment-offer. It is a loss in terms of time, money, efforts, and work. TA managers are in constant search of solution to cope-with this issue. In this paper we have made an attempt to unravel this burgeoning problem by posing two research questions; What factors determine joining decision post-selection in an organization? And; What strategy should TA manager use to make dynamic talent join the organization when selected after rigorous screening and selection process?